The Expression of FoxO1 in Placenta and Omental Adipose Tissue of Gestational Diabetes Mellitus - Xu, Y.; Jin, B.; Sun, L.; Yang, H.; Cao, X.; Zhang, G. (Experimental and Clinical Endocrinology & Diabetes, 2014)
To investigate FoxO1 expression in term placenta and omental adipose tissue between pregnant women with gestational diabetes mellitus (GDM) and those with normal glucose tolerance (control). The relationship between FoxO1 and tumor necrosis factor-α (TNF-α) in cultured trophoblast cells was also investigated.Maternal serum, term placenta and omental adipose tissue were collected from the GDM group (n=20) and the control group (n=20). Serum TNF-α, IL-6 and IL-1β concentration was measured. Fasting plasma glucose (FPG) and fasting serum insulin (FIN) were investigated to calculate an insulin resistance index (HOMA-IR). Immunohistochemistry (IHC) was performed to examine the localization of FoxO1 protein in the placenta and adipose tissue. Real time RT-PCR and Western blotting were used to compare the levels of FoxO1 and TNF-α gene and protein between the 2 groups. Trophoblast cells (HTR-8/SVneo and BeWo cells) were cultured to detect the regulation of TNF-α on FoxO1 expression. The effect of FoxO1 knockdown on TNF-α stimulated expression of pro-inflammatory cytokines was also investigated.Compared to control group, Serum TNF-α, IL-6 and IL-1β concentration was higher in GDM group. FoxO1 was expressed in both the placenta and omental adipose tissue. The gene and protein expression of FoxO1 and TNF-α was higher in the GDM group than the control group in both tissues. The expression of FoxO1 in the placenta was positively correlated with HOMA-IR and TNF-α. Stimulation of TNF-α gene increased the expression of FoxO1 in cultured trophoblast cells. FoxO1 deletion in these cells attenuated TNF-α-induced expression of the pro-inflammatory cytokines IL-1β and IL-6.FoxO1 has a potential role as a pro-inflammatory factor in GDM, and may be involved in the development of IR through interaction with TNF-α.
Keywords: FoxO1; TNF-α; placenta; adipose tissue; gestational diabetes mellitus